Simulation of an adaptive set point controller for multi-zone cooling - Llorente, Cesar A. (Animo Repository, 2007)
The two primary goals of building management control strategies are to minimize operational cost and to promote occupant's comfort and well-being. Current trends in Building Management System (BMS) control strategy, is to learn occupant's thermal comfort preferences and adjust the indoor conditions based on these preferences. Existing global or zone based cooling control strategies do not address individual cooling preference of occupations. Common control strategy is to set the cooling level of a zone for the cooling equipment to maintain, regardless whether the zone is occupied or not. This control strategy wastes energy and insensitive to occupants thermal comfort preferences. This study details the development of an adaptive set point controller for multi-zone air conditioning system that calculates the set point level of multiple cooling zones based on the preferences of the occupants. Simulation results show that the temperature levels in the four cooling zones were maintained based on the individual preference of the occupants. Energy saving potentials of the proposed control strategy was demonstrated through simulations that cooling is carried out only during actual zone occupancy. The control strategy considered occupants' preferences in the temperature preference averaging control strategy of the adaptive ambient air controller.